(untitled) (Biological Sciences - PJSIR, 2004)
Cyclization reactions of biphenyl with dichloropropyltrichlorosilane and dichlorobutyltrichlorosilane in the presence of anhydrous aluminum chloride catalyst gave 9 - (2 - trichlorosilylethyl) fluorene and 9 - methyl - 9 - (2 - trichlorosilylethyl) fluorene along with isomeric uncyclized products. All the compounds were structurally identified by GC / MS, 1H and 13C - NMR spectroscopy.